Silica Quadrangle, Minnesota, 1952: 7.5 Minute Series (Topographic) Map - United States Department of the Interior Geological Survey; State of Minnesota, Iron Range Resources and Rehabilitation Commission (Iron Range Research Center, 1952)
Silica quadrangle topographic map (N4715-W9300/7.5) featuring handwritten notations by Ray Segar in pencil and red ink regarding logging railroad lines and camps in the area between Keewatin and Floodwood. The hand written notations include information on the following: logging camps noted with ‘C.